TEACHERS’ USE OF DICTIONARY-BASED LEARNING IN TEACHING ENGLISH TO YOUNG LEARNERS - Chikyta Anatasya Dita; Muhammad Chairil Imran; Sitti Nurjannah (ADHILINGUA: Journal of Language Education, Lilnguistics and Literature, 2026)
This study aims to analyze the use of dictionary-based learning in teaching English to young learners at a public elementary school. This research employed a qualitative research design. The instruments used in this study were classroom observation and interview. The data were collected through classroom observations and semi-structured interviews with an English teacher to identify how dictionary-based learning was implemented during the teaching and learning process. Based on the data analysis, the results showed that dictionary-based learning was consistently used as a dominant strategy in teaching vocabulary. The teacher required students to bring dictionaries and encouraged them to find word meanings independently before receiving explanations from the teacher. This strategy helped students increase vocabulary awareness, develop learning responsibility, and become more independent learners. However, some students experienced difficulties in understanding dictionary meanings, which required teacher guidance and scaffolding. he findings indicate that dictionary-based learning can enhance students’ engagement and understanding in English lessons. This strategy is important for teachers because it helps create a more effective, active, and meaningful learning environment for young learners. In conclusion, the implementation of dictionary-based learning makes the English learning process more engaging, meaningful, and motivating when supported by appropriate teacher assistance.